(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Agriculture is considered in all parts of the world, especially in developed countries, the main source of livelihood and progress, and it has become wrong or illogical to increase agricultural production either horizontally through reclamation of new non-arable lands or vertically using advanced agricultural methods if agriculture relied on primitive methods. The agricultural mechanization field is concerned with, first and foremost, the comprehensive and integral development of humans and their communities as provided by understandable, scientific, practical and economical means and methods in order to develop and advance their countries and standard of living, as well as the operations training and preparation of human cadres technically and administratively to get filled. The basis of the work of the tractor in the field is to manage and operate agricultural machinery through one of the sources of exploiting the capacity in it. The most used of these sources is the tension bar, and the tension bar is the least efficient of these sources due to its dependence on the interaction between the wheel and the soil. The study of standard performance parameters of agricultural tractor, is reviewed herewith, which may help to the researchers in planning their experiments abut performance mechanics more useful and in right direction to get more accurate results. Traction performance 0.5 for belts and 0.4 for tires, the percentages of difference ranged between 10% and 17% for tire pressure. Tractor performance audits aim to provide information, data and readings to researchers and stakeholders in tractor mechanics for years to come.